Innovation in learning anesthesia nursing care based on the android application “SIASENA” - Annisa, Rully; Ching Cing, Marta Tania Gabriel; Purwanto, Lahan Adi (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: Anesthesiology Nursing Care Services (ASKAN) are used to refer to a series of comprehensive care activities for patients who cannot help themselves due to impaired body function, especially during the anesthesia service process before, during, and after the procedure, or in other situations. The provision of care is carried out through an anesthesia management method approach, which includes the stages of assessment, analysis, problem determination, action/intervention planning, implementation, and evaluation. The implementation of anesthesiology nursing care services (ASKAN) is carried out independently and involves collaboration with anesthesiology specialists, surgeons, and other professional health workers to provide services to patients. The implementation of ASKAN requires anesthesia nurses as one of the health workers involved in providing health services to continue to improve their knowledge and skills. With mobile learning, students have access to learning materials and information from various places and at any time. They are not limited to a certain time or location to learn. The purpose of this study was to produce a prototype and learning model for mobile learning, namely the